Evaluation of postoperative patient satisfaction after covering the nasal dorsum with upper lateral cartilage: "upper lateral closing" - Çağıcı,Can Alper (2019)
Abstract Introduction: Following nasal hump removal during septorhinoplasty, the middle vault should be reconstructed to avoid functional and esthetic problems. Middle vault reconstruction, however, may result in widening of the middle vault and may need a camouflage graft to cover dorsal irregularities. Objective: To present the results of reconstructing the middle vault with a technique that covers the nasal dorsum with upper lateral cartilage, from the viewpoint of patient satisfaction. Methods: Retrospective study of patients who underwent septorhinoplasty that included nasal dorsum closure with upper lateral cartilage from December 1, 2014 to January 31, 2016. Those with postoperative follow-up of less than 3 months were excluded. The final study group included 39 patients. The same surgeon performed all septorhinoplasties. The dorsum was closed using an "upper lateral closing" technique that approximated upper lateral cartilages to each other over the septum. Postoperative patient satisfaction was determined using a visual analog scale and the rhinoplasty outcomes evaluation questionnaire. The questionnaire evaluates patient esthetic and functional satisfaction with the operated nose. High scores indicate improved esthetic results. Results: No dorsal irregularities were seen at postoperative follow-up evaluation of the patients. For esthetic nasal appearance, the median visual analogue scale scores was 86%, and the mean for the questionnaire was 77.03%. Conclusion: The natural dome-shaped anatomy of the nasal dorsum was achieved by approximating the upper lateral cartilages to each other. Closing the dorsum with this technique also covers any dorsal irregularities and results in a smooth dorsum. Patients expressed satisfaction with the esthetic and functional aspects of the smooth, attractive nasal dorsum.